Regulation or revenues: an analysis of local business licences, with a case study of the single business permit reform in Kenya - Devas, Nick; Kelly, Roy (2001)
Licensing of businesses by local governments is a common practice in many countries. While business licensing has its origins in regulation, it is often seen as little more than a revenue source for local government. This article reviews the potentially conflicting objectives of regulation and revenue generation, and outlines the various forms which local taxation of business has taken in a number of countries. In practice, the regulatory aspects of local business licensing in many developing countries are ineffective at best and counterproductive at worst, and there are pressures to sweep away most local business licences as part of deregulatory reform. Yet local governments in many countries are in dire need of revenue sources in order to finance local service provision. The article analyses the reforms that have been introduced to business licensing in Kenya. There, traditional business licences have been replaced with a Single Business Permit, with the twin objectives of increasing local revenues and reducing regulatory compliance costs on businesses. Initial results suggest that, while there have been some initial start-up problems, both these objectives are being achieved. - Reproduced.
Keywords: Case studies; Local government - Kenya; Local government